We've Come a Long Way, Baby (But We're Not There Yet): Gender Past, Present, and Future. Issue 1 (28th January 2016) - Liben, Lynn S.
Abstract : Gender has long been, and continues to be, a powerful predictor of developmental experiences and outcomes. Observations drawn from personal history, developmental science, and life beyond the academy show that historically, gender constraints have diminished in some ways, but remain robust in others. Reviewed are children's constructive processes that—in interaction with the embedding ecology—foster the emergence and persistence of gendered phenomena. Reviews of interventions designed to increase girls' science participation demonstrate the need to evaluate both intended and unintended program consequences. Discussion of the single‐sex schooling debate shows the importance of foundational conceptualizations of gender, and illuminates research‐to‐policy processes. After identifying newly emerging gender conceptualizations, the concluding section highlights the need to consider how gender conceptualizations do and should affect science and society.